THE INFLUENCE OF SELF- REGULATED LEARNING AND LEARNING ATTITUDE TOWARDS THE TENTH GRADE STUDENTS’ READING ABILITY - Yesi Afriani (Universitas PGRI Palembang, 2022)
This research investigates the influence of self-regulated learning and learning attitude towards the tenth grade students’ reading ability of state SMK Negeri 8 Palembang. This study the researcher use quantitative technique and conduct utilizing a factorial design. The sample of this study are all of tenth grade students of SMK Negeri 8 Palembang that consist of 30 student for experimental group and 30 students for control group. Data collection techniques used questionnaires and tests. For the data analysis technique to find out the influence and the interaction effect used SPSS 20, The finding of this study are: (1) There are not significant influence of self-regulated learning and Learning attitude towards tenth grade students’ Reading Ability of those who have high motivation and those who have low motivation; (2) There was not significant interaction effect of Self-regulated Learning and Learning Attitude towards the students’ Reading Ability at SMK Negeri 8 Palembang.